Tumble! Splat! Helping Users Access and Manipulate Occluded Content in 2D Drawings - Ramos, Gonzalo; Robertson, George; Czerwinski, Mary; Tan, Desney; Baudisch, Patrick; Hinckley, Ken; Agrawala, Maneesh (AVI '06 Proceedings of the working conference on Advanced visual interfaces, 2006)
Accessing and manipulating occluded content in layered 2D drawings can be difficult. This paper characterizes a design space of techniques that facilitate access to occluded content. In addition, we introduce two new tools, Tumbler and Splatter, which represent unexplored areas of the design space. Finally, we present results of a study that contrasts these two tools against the traditional scene index used in most drawing applications. Results show that Splatter is comparable to and can be better than the scene index. Our findings allow us to understand the inherent design tradeoffs, and to identify areas for further improvement.